Understanding the effects of techno-stress on the performance of banking staff - Owusu-Ansah, S.; Azasoo, J.Q.; Adu, I.N. (Int. J. Business Continuity and Risk Management, 2016)
The technological revolution has undoubtedly brought about many changes in the modern workplace. Although it has allowed work to be carried out faster and more efficiently, many employees are not comfortable with its implementation since it involves change and uncertainty. As a result, users experience technological stress (techno-stress), which may have negative consequences on work places like commercial banks. This paper aims at investigating the effects of techno-stress on employees in the banking sector. A survey methodology that involves self-administered questionnaires to solicit data from 400 banking staff of commercial banks was employed. The employees revealed that ICTs create mental pressure, sense of anxiety and pessimism, as they have to keep up with the fast advancing pace of the new ICTs. Our study reveals that techno-stress has a negative impact on employee performance. It is recommended that the management of commercial banks, and IT professionals provide a better environment, alternative power supply and adequate training programs.
Research Article
Keywords: techno-stress; information technology; information systems